Comprehensive genetic analysis by targeted sequencing identifies risk factors and predicts patient outcome in Mantle Cell Lymphoma: results from the EU-MCL network trials - Khouja, Mouhamad; Jiang, Linmiao; Pal, Karol; Stewart, Peter James; Regmi, Binaya; Schwarz, Martin; Klapper, Wolfram; Alig, Stefan K; Darzentas, Nikos; Kluin-Nelemans, Hanneke C; Hermine, Olivier; Dreyling, Martin; et al. (Leukemia, 2024)
Recent studies highlighted genetic aberrations associated with prognosis in Mantle Cell lymphoma (MCL), yet comprehensive testing is not implemented in clinical routine. We conducted a comprehensive genomic characterization of 180 patients from the European MCL network trials by targeted sequencing of peripheral blood DNA using the EuroClonality(EC)-NDC assay. The IGH::CCND1 fusion was identified in 94% of patients, clonal IGH-V-(D)-J rearrangements in all, and 79% had ≥1 somatic gene mutation. The top mutated genes were ATM, TP53, KMT2D, SAMHD1, BIRC3 and NFKBIE. Copy number variations (CNVs) were detected in 83% of patients with RB1, ATM, CDKN2A/B and TP53 being the most frequently deleted and KLF2, CXCR4, CCND1, MAP2K1 and MYC the top amplified genes. CNVs and mutations were more frequently observed in older patients with adverse impact on prognosis. TP53mut, NOTCH1mut, FAT1mut TRAF2del, CDKN2A/Bdel and MAP2K1amp were linked to inferior failure-free (FFS) and overall survival (OS), while TRAF2mut, EGR2del and BCL2amp related to inferior OS only. Genetic complexity (≥3 CNVs) observed in 51% of analysed patients was significantly associated with impaired FFS and OS. We demonstrate that targeted sequencing from peripheral blood and bone marrow reliably detects diagnostically and prognostically important genetic factors in MCL patients, facilitating genetic characterization in clinical routine.
Keywords: Genetic Testing; Male; Lymphoma, Mantle-Cell; mutace; DNA Copy Number Variations; Risk Factors; genetické testování; High-Throughput Nucleotide Sequencing; prognóza; lymfom z plášťových buněk; Adult; Aged; dospělí; mužské pohlaví; senioři; variabilita počtu kopií segmentů DNA; senioři nad 80 let; lidé; ženské pohlaví; Biomarkers, Tumor; Humans; vysoce účinné nukleotidové sekvenování; rizikové faktory; Aged, 80 and over; Prognosis; Mutation; Female; lidé středního věku; nádorové biomarkery; Middle Aged